Improvement of Solubility and Dissolution Rate of Sirolimus by Solid Dispersions in Combination with Surface Adsorbent - Patel, Pranav V.; Parmar, Hardeepsinh H.; Panchal, Shital S. (Drug Delivery Letters, 2013)
Sirolimus has a poor solubility in water ranging from 2-6 μg/mL. The mean bioavailability is approximately 14%. The present study was carried out with a view to enhance the dissolution rate of poorly water-soluble drug sirolimus using Gelucire® as carriers and lactose monohydrate as an adsorbent. A combination of melt and adsorption techniques was employed for the preparation of solid dispersions (SD) to make final product free flowing. Phase solubility study was conducted to evaluate the effect of carriers on aqueous solubility of sirolimus. In order to elucidate the mechanism of dissolution enhancement, solid state characteristics were investigated using Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC) and powder X-ray diffraction (XRD). Mathematical modeling of in vitro dissolution data of optimised batch indicated the best fitting with Korsemeyer–Peppas model and the drug release kinetics primarily as fickian diffusion. All prepared solid dispersions showed dissolution improvement compared to pure drug. Almost similar dissolution profile was obtained as a function of storage time; this can be explained by no change in XRD and DSC patterns after 45 days of storage period.
Keywords: Dissolution enhancement